2010
DOI: 10.1007/s10751-010-0235-y
|View full text |Cite
|
Sign up to set email alerts
|

A priori calculations of hyperfine interactions in highly ionized atoms: g-factor measurements on aligned pico-second states populated in nuclear reactions

Abstract: Abstract. Calculations of hyperfine interaction strength and life-times of states in highly ionized atoms, using the GRASP atomic structure package are reported. The calculations aim at providing calibration at Recoil-in-Vacuum nuclear excited states g-factor measurements. The method is outlined and results compared with experiment. Inclusion of decay of higher electronic states is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
(5 reference statements)
0
15
0
Order By: Relevance
“…Combined with accurate measurements of hyperfine structure splittings, calculated atomic parameters can be used to extract nuclear quadrupole moments Q [3]. In a different setting the hyperfine interaction is a key factor in determining excited state nuclear g-factors from recoil-in-vacuum experiments [4]. Hyperfine interaction is also important in astrophysics, high resolution solar, stellar spectra reveal isotope shifts and hyperfine structures of many spectral lines.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with accurate measurements of hyperfine structure splittings, calculated atomic parameters can be used to extract nuclear quadrupole moments Q [3]. In a different setting the hyperfine interaction is a key factor in determining excited state nuclear g-factors from recoil-in-vacuum experiments [4]. Hyperfine interaction is also important in astrophysics, high resolution solar, stellar spectra reveal isotope shifts and hyperfine structures of many spectral lines.…”
Section: Introductionmentioning
confidence: 99%
“…To date we have used a semiempirical method to define G k (|g|τ) [1,2,3,8,9]. It appears, however, that ab initio calculations of the relevant atomic physics may be possible in future [10,11]. This experimental and calculational effort, along with the current open questions, has been reviewed recently [9].…”
Section: Methodsmentioning
confidence: 99%
“…Stone et al [39] have reported such calculations for Mo, Ru and Pd ions recoiling into vacuum with velocity v/c ∼ 0.05, and more recently for 54,56 Fe ions at v/c ∼ 0.08 [40]. This static model can then be improved by including the effect of atomic transitions, based on the calculated atomic level lifetimes, which Stone et al also explored [39,40]. Chen et al [21] have taken the calculations further by implementing a Monte Carlo method to evaluate the effect of atomic transitions and applying it to the tellurium isotopes.…”
Section: E Status Of Ab Initio Riv Calculationsmentioning
confidence: 99%